Epicardial and paracardial adipose tissue volume and attenuation: association with high-risk coronary plaque on computed tomographic angiography in the ROMICAT II trial - Lu, Michael T.; Park, Jakob; Ghemigian, Khristine; Mayrhofer, Thomas; Puchner, Stefan B.; Liu, Ting; Fleg, Jerome L.; Udelson, James E.; Truong, Quynh A.; Ferencik, Maros; Hoffmann, Udo (Atherosclerosis, 2016)
Background and aims - To determine whether epicardial (EAT) and paracardial adipose tissue (PAT) volume and attenuation are associated with high-risk coronary plaque features. - Methods - In subjects with suspected acute coronary syndrome (ACS) enrolled in the ROMICAT II trial, EAT and PAT volumes indexed to body surface area (BSA) and attenuation were measured on non-contrast coronary artery calcium score (CACS) CT. High-risk plaque features (napkin-ring sign, positive remodeling, low density plaque, spotty calcium) and stenosis were assessed on coronary CT angiography (CTA). The association of EAT and PAT volume and attenuation with high-risk plaque and whether this was independent of clinical risk assessment, CACS and significant coronary artery disease (CAD) was determined. - Results - Of 467 (mean 54 ± 8 yrs, 53% male) with CACS and CTA, 167 (36%) had high-risk plaque features. Those with high-risk plaque had significantly higher indexed EAT (median 59 (Q1-Q3:45-75) cc/m2 vs. 49 (35-65) cc/m2, p < 0.001) and PAT volume (median:51 (36-73) cc/m2 vs. 33 (22-52) cc/m2, p < 0.001). Higher indexed EAT volume was associated with high-risk plaque [univariate OR 1.02 (95%-CI:1.01-1.03) per cc/m2 of EAT, p < 0.001], which remained significant [univariate OR 1.04 (95%-CI:1.00-1.08) per cc/m2 of EAT, p = 0.040] after adjustment for risk factors, CACS, and stenosis ≥50%. Higher indexed PAT volume was associated with high-risk plaque in univariate analysis [OR 1.02 (1.01-1.03) per cc/m2 of PAT, p < 0.001], though this was not significant in multivariate analysis. At a threshold of >62.3 cc/m2, EAT volume was associated with high-risk plaque [univariate OR 2.50 (95%-CI:1.69-3.72), p < 0.001)], which remained significant [OR 1.83 (95%-CI:1.10-3.05), p = 0.020] after adjustment. Subjects with high-risk plaque had lower mean attenuation EAT (−88.1 vs. −86.9 HU, p = 0.008) and PAT (−106 vs. −103 HU, p < 0.001), though this was not significant in multivariable analysis. - Conclusions - Greater volumes of EAT are associated with high-risk plaque independent of risk factors, CACS and obstructive CAD. This observation supports possible local influence of EAT on development of high-risk coronary plaque.
Gesehen am 19.05.2020